MANAGEMENT APPROACHES TO INCREASE BUSINESS EFFECTIVENESS IN THE MANUFACTURING SECTOR OF THE GEM AND JEWELRY INDUSTRY IN THAILAND - Kotsopa, Tanyanan; วีระญาณนนท์, เกียรติชัย; ธรรมชาลัย, อนันต์ (Thai Interdisciplinary and Sustainability Review, 2023)
The objectives of this research are 1) to investigate the current state of business operations, competition, the external environment, various management problems, and business effectiveness in the manufacturing sector of the gem and jewelry industry in Thailand; 2) to investigate the business attributes and business management factors that influence business effectiveness; and 3) to analyze and propose management approaches to increase the effectiveness of the businesses. The results of the research found that the external and internal business environment encountered problems with shortages of domestic raw materials, high-priced machinery and equipment, production processes, and skilled labor and production expertise. The results of the comparison of business effectiveness when classified according to business characteristics were found to be statistically significantly different when classified according to registered capital, number of employees, duration of business operations, and location. The results of the multiple regression analysis found that business management factors such as structure, system, personnel, management style, and shared values have a statistically significant effect on business effectiveness. From SWOT analysis and synthesis into guidelines using TOWS Matrix, a total of 8 approaches were obtained.